An inventory model for deteriorating items with time-dependent demand and time-varying holding cost under partial backlogging - Vinod Kumar Mishra; Lal Sahab Singh; Rakesh Kumar (Journal of Industrial Engineering International, 2013)
In this paper, we considered a deterministic inventory model with time-dependent demand and time-varying holding cost where deterioration is time proportional. The model considered here allows for shortages, and the demand is partially backlogged. The model is solved analytically by minimizing the total inventory cost. The result is illustrated with numerical example for the model. The model can be applied to optimize the total inventory cost for the business enterprises where both the holding cost and deterioration rate are time dependent.
Keywords: 650; inventory model; deteriorating items; shortage; time-dependent demand; time-varying holding cost